Coronary heart disease mortality trends during 50 years as explained by risk factor changes: The European cohorts of the Seven Countries Study. (29th August 2020) - Menotti, Alessandro; Puddu, Paolo E; Kromhout, Daan; Kafatos, Anthony; Tolonen, Hanna
Abstract: Objectives: The purpose of this study was to relate risk factor changes during decades with 50-year coronary heart disease mortality in European cohorts of middle-aged men of the Seven Countries Study. Material and methods: In the 1950s–early 1960s, nine cohorts of 6518 men aged 40–59 years were examined in five European countries. Smoking habits, systolic blood pressure and serum cholesterol were measured at entry and five times during the next 35 years and a comprehensive Risk Factor Change Score was created. Coronary heart disease mortality data was collected during a 50-year follow-up, modelled by the Weibull distribution, whose shape (Weibull shape) was related to the Risk Factor Change Score by linear regression. Results: The Risk Factor Change Score showed slight declines in the Finnish and Dutch cohorts, moderate or large increases in the other cohorts. These effects were related to a decrease of smoking habits in all cohorts, an increase of blood pressure in all cohorts except East Finland, a decrease of serum cholesterol in Finland and the Netherlands, whereas serum cholesterol increases were slight in Italy and large in Serbia and Greece. Weibull distribution shape for coronary heart disease mortality showed slight deceleration in one Finnish and the Dutch cohorts, large acceleration in the Serbian and Greek cohorts. The correlation coefficient of the Risk Factor Change Score versus Weibull shape for the nine cohorts was 0.78 ( R 2  = 0.60; p  = 0.0132). Conclusions: Spontaneous long-term changes of major coronary risk factor levels were associated with changes in the same direction of coronary heart disease mortality risk modelled by the Weibull distribution, expressing a kind of 'natural experiment' with an outcome that matches those of controlled preventive trials.